Critical intersex - Holmes, Morgan (Ashgate, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Section: 1 vol. (XIV-257 p.) ; 24 cm.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes

The coming-out process of young lesbian and bisexual women: Are there butch/femme differences in sexual identity development? - Rosario, Margaret; Schrimshaw, Eric W; Hunter, Joyce; Levy-Warren, Anna (Archives of sexual behavior, 2009)
Research on lesbian and bisexual women has documented various biological and behavioral differences between butch and femme women. However, little research has examined whether differences exist in sexual identity development (i.e., the coming-out process). The present study examined longitudinally potential butch/femme differences in sexual identity formation and integration among an ethnically diverse sample of 76 self-identified lesbian and bisexual young women (ages 14–21 years). A composite measure of butch/femme identity classified 43% as butch and 51% as femme. Initial comparisons found butch/femme differences in sexual identity (i.e., nearly all butches identified as lesbian, but about half of femmes identified as bisexual), suggesting the need to examine this confound. Comparisons of lesbian butches, lesbian femmes, and bisexual femmes found that lesbian butches and femmes generally did not differ on sexual identity formation, but they differed from bisexual femmes. Lesbian butches and femmes had sexual behaviors and a cognitive sexual orientation that were more centered on women than those of bisexual femmes. With respect to sexual identity integration, lesbian butches were involved in more gay social activities, were more comfortable with others knowing about their homosexuality, and were more certain, comfortable, and accepting of their sexual identity than were bisexual femmes. Fewer differences were found between lesbian femmes and bisexual femmes or between lesbian butches and lesbian femmes. The findings suggest that sexual identity formation does not differ between butch or femme women, but differences are linked to sexual identity as lesbian or bisexual. Further, the findings that lesbian femmes sometimes differed from lesbian butches and at other times from bisexual femmes on sexual identity integration suggest that neither sexual identity nor butch/femme alone may explain sexual identity integration. Research examining the intersection between sexual identity and butch/ femme is needed.
Number: 1
Keywords: butch/femme; discipline; identité sexuelle; identités LGBTQIA2+; personnes bisexuelles; personnes lesbiennes; ressource en ligne; sciences humaines; sexologie; sexualité; thématiques